Fluctuations in Stock Prices of Companies in Indonesia as an Impact of Organizing Presidential Elections: Time Series Component Analysis: Cyclical Variation - Ningrum, Herawati; Mediawati, Elis (Jurnal Riset Multidisiplin dan Inovasi Teknologi, 2024)
The objective of this study was to determine how non-economic events, such as the presidential election affect the Composite Stock Price Index. A descriptive quantitative method was used to collect secondary data from the Indonesia Stock Exchange (IDX) website. The data used is a historical data set from 1999 to 2019. The data was taken from the daily closing price of LQ45 on the JCI (Composite Stock Price Index). Analysis techniques using time series analysis. Data analysis used ARIMA (Autoregressive Integrated Moving Average) model. The study found that company stock prices changed due to presidential elections in 1999, 2004, 2009, and 2014. Suggestions for further research are to find techniques used as well as to include other elements that further influence investor decisions.